Plant Bioactives as Inhibitors of Matrix Metalloproteases and their Anti-skin Photoaging Potential - Baghel, Madhuri; Badwaik, Hemant; Patil, Sangeeta; a, Azajuddin (Pharmacognosy Reviews)
Because skin aging is so important in terms of looks, research into preventive and therapeutic treatments has proliferated. Ultraviolet (UV) radiation alters the extracellular matrix (ECM), stimulates matrix metalloproteinases (MMPs), while diminishes the elastin and collagen. MMPs are zinc-containing endo-peptidases that help to restore the ECM. The MMP families, based on substrate structure and specificity are: a) collagenases b) gelatinases c) stromelysins d) matrilysins and e) membrane type MMPs. Except for matrilysin, these enzymes contains haemopexin, propeptide and catalytic domains. Among the photoprotective strategies used to prevent and/or treat photoaging are topical sunscreens that work at the molecular level. We investigate photoaging mechanisms and plant bioactives. Skin photoaging is primarily caused by UV radiation from the sun, as it produces reactive oxygen species and disrupt DNA/cellular equilibrium, alter signal transduction pathways and inflammatory cascades, as well as immunosuppression and ECM restoration. Antiaging studies recently predicted the usage of natural chemicals from ancient civilizations. The sun protection factor and antioxidant properties of plants help prevent wrinkles and give the skin a youthful glow. Thus, the current study focuses on the development of anti-photoaging therapies that target specific MMPs connected to skin aging and wrinkle generation. We explored MMP suppressors or inhibitors found in plants.
Keywords: MMPs; Plant Bioactives; Photoaging; Anti skinaging; Reactive oxygen species